Development of a Two- Tier Higher Order Thinking Skill (HOTS) Test Instrument Based on IBT on Chemical Equilibrium Material for SMA/MA Students - Zikra Effendi; Andromeda Andromeda (Universitas Negeri Padang, 2022)
HOTS is an ability that can transfer, connect one material with other material, process information and solve problems obtained from the information creatively and critically. Higher Order Thinking Skill (HOTS) are abilities that must be prossessed by students in facing global competition in the 21st century industrial revolution 4.0 in accprdence with the 2013 curriculum. This study aims to produce a test instrument for higher order thinking skill (HOTS) in chemical equilibrium and determine the level of validity and its reliability. This tyepe of research is research and development (R&D) and use the research model that has been developed by treagust (1988). The results showed that the value of the validity of the content instrument test was 1 and the validity of the construct instrument was 95% in the material aspect, 94% on the presentation aspect, 96% on the language aspect, and 08% on the additional rules. The instrument reliability tes coefficient is 0,85 for the question (fisrt tier) and 0,89 for the reason (second tier).